URGENSI PEMBAHARUAN HUKUM KELUARGA ISLAM : Analisis Dalam Batas Usia Menikah, Poligami Dan Hak Ibu-Anak Pasca Perceraian - Kausar, Ira; Syarifuddin, Syarifuddin; Murtadho , Ali (MAQASHID, 2025)
The reform of Islamic family law is an urgent matter that requires the government's full attention. The reality of the times and the diversity of issues make it difficult to apply the old rules. Issues such as the minimum age for marriage, polygamy, and the rights of mothers and children after divorce require in-depth analysis through a qualitative approach using descriptive-analytical methods that provide a comprehensive overview, as well as literature studies, in order to find solutions that are in line with the times. A comprehensive discussion is needed so that Indonesian society has strong, up-to-date regulations that address future challenges related to resolving issues such as the minimum age for marriage, polygamy, and the rights of mothers and children after divorce.